2015
DOI: 10.3109/15622975.2015.1012224
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of anti-Toxoplasma gondiiand anti-Borreliaspecies antibodies in patients with schizophrenia: a case–control study from western Turkey

Abstract: Our data showed the rate of Toxoplasma antibodies was higher in the case group, while the rate of Borrelia antibodies was higher in the control group. In both groups the high rates of seropositivity for Toxoplasma gondii and Borrelia sp. is thought to be due to neglect of personal hygiene. The present study also is the first to examine the association between Borrelia sp. and schizophrenia. Further studies are needed to determine whether there is an association between Borrelia sp. and schizophrenia or not.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…There are several reports of higher T. gondii serological prevalence in patients with schizophrenia (Cetinkaya et al ., 2007; Tamer et al ., 2008; Dogruman et al ., 2009; Tanyüksel et al ., 2010; Çelik et al ., 2015; Cevizci et al ., 2015; Karabulut et al ., 2015; Yuksel et al . 2010) and patients with chronic renal failure (Yazar et al ., 2003; Ocak et al ., 2005), neoplastic disorders (Yazar et al ., 2004), cirrhosis (Ustun et al ., 2004; Atilla et al ., 2015), chronic heart failure (Yazar et al ., 2006), reactive arthritis (Sert et al ., 2007), idiopathic Parkinson's disease (Celik et al ., 2010), Alzheimer's disease (Kusbeci et al ., 2011) and Multiple Sclerosis (Koskderelioglu et al ., 2017); however, the sample size and appropriate controls were lacking for cause effect relationship.…”
Section: Toxoplasmosis In Humansmentioning
confidence: 99%
“…There are several reports of higher T. gondii serological prevalence in patients with schizophrenia (Cetinkaya et al ., 2007; Tamer et al ., 2008; Dogruman et al ., 2009; Tanyüksel et al ., 2010; Çelik et al ., 2015; Cevizci et al ., 2015; Karabulut et al ., 2015; Yuksel et al . 2010) and patients with chronic renal failure (Yazar et al ., 2003; Ocak et al ., 2005), neoplastic disorders (Yazar et al ., 2004), cirrhosis (Ustun et al ., 2004; Atilla et al ., 2015), chronic heart failure (Yazar et al ., 2006), reactive arthritis (Sert et al ., 2007), idiopathic Parkinson's disease (Celik et al ., 2010), Alzheimer's disease (Kusbeci et al ., 2011) and Multiple Sclerosis (Koskderelioglu et al ., 2017); however, the sample size and appropriate controls were lacking for cause effect relationship.…”
Section: Toxoplasmosis In Humansmentioning
confidence: 99%
“…These variables are essential risk factors for T. gondii seroconversion. Direct contact with infected cats is the primary cause of T. gondii seroconversion; Consumption of unclean water could cause toxoplasmosis via T. gondii oocysts; Ingestion of contaminated raw meat may cause infection with T. gondii cysts [30][31][32]. In addition to the risk factors that could explain the possible association of toxoplasmosis and schizophrenia, physiological mechanisms could strengthen this correlation by the fact that the presence of Toxoplasma in the CNS that certainly causes adequate tropism and deregulation of neurotransmitter gene expression, promoting the development of psychoses, including schizophrenia [24].…”
Section: Discussionmentioning
confidence: 99%
“…(2) Alcohol abuse generally impairs the immune response [12] thereby heightening the risk for severe infectious diseases such as tuberculosis [13] and community-acquired pneumonia [14]. (3) For schizophrenia and related disorders, viral infections were reported (e.g., Herpes simplex , Epstein-Barr , Arboviruses , Polio ) [15], as well as infections with Toxoplasma gondii and Borrelia [16]. For patients with Alzheimer’s disease, studies showed a heightened risk for bacterial infections with spirochetes and Chlamydophilia pneumoniae [17,18].…”
Section: Introductionmentioning
confidence: 99%